2014
DOI: 10.2527/jas.2013-6555
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient digestibility of lentil and regular- and low-oligosaccharide, micronized full-fat soybean fed to grower pigs1

Abstract: A study was conducted to determine the standardized ileal digestibility (SID) of AA and calculate the NE value for regular-oligosaccharide, micronized full-fat soybean (R-MFFSB), low-oligosaccharide, micronized full-fat soybean (LO-MFFSB), lentil, and enzymatically hydrolyzed casein (EHC) for growing pigs. Six ileal-cannulated barrows (31.4 kg BW) were fed 6 diets in a 6 × 6 Latin square. Five diets were cornstarch based, containing either soybean meal (SBM), R-MFFSB, LO-MFFSB, or EHC as sole protein source or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 31 publications
3
10
2
Order By: Relevance
“…Also, the TI activity of the CPCC was higher than the value (<1.0 TIU/ mg) that was reported by Almeida et al (2013) for canola meal, which is another co-product of the Brassica family. The TI activity of the SBM was similar to the values (3.20-6.21 TIU/mg) that were reported by others (Valencia et al, 2008;Goebel and Stein, 2011;Perryman and Dozier III, 2012;Woyengo et al, 2014). In addition to TI activity, camelina co-products, like most of the other co-products of the Brassica family, contain high levels of glucosinolates (Almeida et al, 2013;Kahindi et al, 2014), which reduces voluntary feed intake because of their bitterness (Lee and Hill, 1983;Mailer et al, 2008).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Also, the TI activity of the CPCC was higher than the value (<1.0 TIU/ mg) that was reported by Almeida et al (2013) for canola meal, which is another co-product of the Brassica family. The TI activity of the SBM was similar to the values (3.20-6.21 TIU/mg) that were reported by others (Valencia et al, 2008;Goebel and Stein, 2011;Perryman and Dozier III, 2012;Woyengo et al, 2014). In addition to TI activity, camelina co-products, like most of the other co-products of the Brassica family, contain high levels of glucosinolates (Almeida et al, 2013;Kahindi et al, 2014), which reduces voluntary feed intake because of their bitterness (Lee and Hill, 1983;Mailer et al, 2008).…”
Section: Discussionsupporting
confidence: 86%
“…Also, basal ileal endogenous AA losses were comparable to values reported by Shi et al (2015) for growing pigs fed N-free diet. However, the basal ileal endogenous AA losses were greater than the values that were reported by Zhai and Adeola (2011), Woyengo et al (2014), and Woyengo et al (2016b) for growing pigs fed N-free diet. Recently, Adeola et al (2016) reviewed the methods of estimation of basal ileal endogenous AA losses in pigs, and concluded that basal ileal endogenous AA loss values from pigs fed N-free diet are lower than those from pigs fed low casein cornstarch-based diet.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…The nitrogen retained in diets with co-products is not affected when the imbalances in the amino acid concentrations or the post-absorptive energy metabolism of diets is taken into account [7]. In recent years, the ME or the DE systems have been substituted gradually by the NE system in pig husbandry of North America and Europe [8].…”
Section: Introductionmentioning
confidence: 99%
“…Other potential dietary protein sources may be of plant origin, such as peanut flour (PF) and full-fat soybean (FFSB). Although FFSB contains high concentrations of crude protein (CP) and energy [7,8], it also contains a considerable amount of trypsin inhibitors that limits its use in swine diets. Alternatively, PF produced from dehulling and grinding peanuts contains high CP [9], which makes it another potentially valuable protein source for pigs.…”
Section: Introductionmentioning
confidence: 99%